PENGEMBANGAN SISTEM INFORMASI PENGARSIPAN SURAT BERBASIS WEBSITE MENGGUNAKAN CODEIGNITER 4 - Risti Fadila, Riva; Yopi Nugraha (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The management of the archive of incoming and outgoing letters that is not the best can result in delays in document searches, recording errors, and reduce the efficiency of the administrative stages. Therefore, this study intends to expand the website-based letter archiving information system at PT Tech Mayantara Asia to improve the effectiveness of archive management. The system was developed using the CodeIgniter 4 framework in an Agile manner, which allows the development process to be carried out in stages through multiple sprints so that each feature can be evaluated and refined based on user feedback. The system provides features for managing incoming letters, outgoing letters, decision letters, circulars, user management, mail history, and report presentation in one integrated database. The results of the development show that the system is able to speed up the process of recording and searching archives, improve the accuracy and accuracy of document management, reduce the risk of data loss, and produce more structured reports. In addition, a more user-friendly interface and better integration of features support improved efficiency of enterprise administration. Therefore, the developed system can be an effective digital solution for PT Tech Mayantara Asia and has the potential to be applied to other agencies that have web-based mail archive management needs.